High-temperature-resistant stainless steel wire for turbine outer ring sealing gasket of an aero-engine and preparation method thereof
Patent Information
- Application Number
- CN202611173167.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]目前,现有涡轮密封垫用不锈钢丝多采用常规304、316L不锈钢材质,该类不锈钢丝常温力学性能优异,但高温耐受极限仅为800℃左右,在发动机涡轮极端高温工况下易出现晶粒粗化、高温软化、塑性蠕变等问题,长期使用后会出现密封垫松弛、变形、开裂,导致密封间隙增大、燃气泄漏量超标,大幅降低发动机运行稳定性
本申请通过精准复配La、Ce、Y三元稀土组分并限定其特定配比含量,使三种稀土元素形成协同强化效应,且使稀土原子可优先富集于合金晶界、缺陷空位及相界面处,大幅降低晶界界面能,有效抑制高温服役过程中晶界迁移与晶粒异常长大;同时三元稀土复合体系可优先与熔体及基体中的O、S、P等有害杂质反应生成高熔点、高稳定性的稀土化合物,有效消除晶界有害杂质偏析带来的晶界脆化缺陷,显著净化并强化晶界结构。该三元稀土复合体系可同步提升合金的高温晶界强度、位错运动阻力及晶格稳定性,大幅改善不锈钢丝高温抗蠕变、抗热疲劳与抗高温氧化冲刷性能,解决了传统不锈钢丝高温下晶界易弱化、组织易劣化、性能衰减快的技术难题。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of metal material processing technology, and more specifically, it relates to a high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine and its preparation method. Background Technology
[0002] As a core sealing component of the turbine, the turbine outer ring of an aero-engine operates under conditions of high temperature (1000℃-1300℃), high-pressure gas impact, and high-frequency mechanical vibration. Its matching sealing gasket is a crucial component for preventing turbine gas leakage, ensuring engine boosting efficiency, and improving the overall thrust-to-weight ratio. The core material of the sealing gasket is stainless steel wire, whose high-temperature resistance, high-temperature strength, creep resistance, and resistance to gas erosion directly determine the sealing reliability and service life of the turbine outer ring.
[0003] Currently, most stainless steel wires used for turbine gaskets are made of conventional 304 or 316L stainless steel. While these wires have excellent mechanical properties at room temperature, their high-temperature resistance limit is only around 800℃. Under the extreme high-temperature conditions of engine turbines, they are prone to problems such as grain coarsening, high-temperature softening, and plastic creep. After long-term use, the gaskets may loosen, deform, and crack, leading to increased sealing gaps, excessive gas leakage, and a significant reduction in engine operating stability. Furthermore, the existing stainless steel wire manufacturing process is simplistic, employing only conventional melting, drawing, and simple annealing. This results in poor surface density, a weak anti-oxidation coating, insufficient resistance to high-temperature gas erosion and thermal fatigue, and uneven grain distribution within the wire, leading to poor elastic recovery after weaving into a gasket, making it unsuitable for the high-frequency vibration conditions of the turbine outer ring.
[0004] While some existing high-temperature alloy steel wires possess high-temperature resistance, they suffer from drawbacks such as excessive hardness, insufficient toughness, difficulty in weaving, and high cost. Furthermore, mass production of sealing gaskets is prone to issues like wire breakage and uneven weaving gaps, severely impacting sealing accuracy. In summary, there is a current lack of a stainless steel wire that combines high-temperature resistance, high-temperature creep resistance, excellent toughness, and formability to meet the extreme operating conditions required for turbine outer ring sealing gaskets in aero-engines. Therefore, there is an urgent need to develop a high-temperature resistant stainless steel wire for aero-engine turbine outer ring sealing gaskets and its preparation method. Summary of the Invention
[0005] To address the technical problems mentioned in the background art, this application provides a high-temperature resistant stainless steel wire for a turbine outer ring sealing gasket in an aero-engine.
[0006] In a first aspect, this application provides a high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine, employing the following technical solution: A high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine, comprising the following chemical composition by mass percentage: C: 0.03-0.08%, Cr: 18.0-22.0%, Ni: 30.0-35.0%, Co: 8.0-12.0%, Mo: 2.5-4.0%, W: 1.5-3.0%, Al: 0.8-1.5%, Ti: 1.8-2.8%, Nb: 0.5-1.2%, Ta: 0.3-0.5%, B: 0.005-0.008%, Zr: 0.03-0.05%, rare earth components: 0.1-0.3%, with the balance being Fe and unavoidable impurities.
[0007] Preferably, in the rare earth component, the mass ratio of La, Ce, and Y satisfies: 2m Ce =3m La And 2m Y =m La +m Ce ; where m La m Ce m Y These represent the masses of La, Ce, and Y in the rare earth components, respectively.
[0008] Preferably, the stainless steel wire comprises, by mass percentage, the following chemical composition: C: 0.03-0.06%, Cr: 19.0-21.0%, Ni: 32.0-33.0%, Co: 9.0-11.0%, Mo: 2.8-3.5%, W: 2.2-2.8%, Al: 1.0-1.3%, Ti: 2.0-2.5%, Nb: 0.7-0.9%, Ta: 0.35-0.45%, B: 0.006-0.007%, Zr: 0.035-0.045%, rare earth components: 0.15-0.25%, with the balance being Fe and unavoidable impurities.
[0009] Secondly, this application also provides a method for preparing high-temperature resistant stainless steel wire for turbine outer ring sealing gaskets in aero-engines, comprising the following preparation steps: A method for preparing high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine includes the following preparation steps: Each raw material component is weighed according to mass percentage, and then subjected to vacuum melting and casting, homogenization heat treatment, multi-pass hot rolling and forging, gradient wire drawing, segmented high-temperature annealing modification, and plasma anti-oxidation coating treatment to obtain high-temperature resistant stainless steel wire for turbine outer ring sealing gaskets of aero-engines.
[0010] Preferably, the vacuum melting ingot is specifically performed by: vacuum melting for 40-60 minutes under vacuum conditions of ≤0.05Pa and 1580-1620℃, followed by refining and casting to obtain an alloy ingot.
[0011] Preferably, the refining temperature is 1600-1630℃ and the refining time is 10-15 min.
[0012] Preferably, the casting process specifically involves casting using a water-cooled copper mold at a casting rate of 8-12 kg / min and a mold cooling water temperature of 25-35°C.
[0013] Preferably, the homogenization heat treatment specifically involves heating the alloy ingot to 1180-1220°C at a heating rate of 8-12°C / min, holding it at that temperature for 8-10 hours, and then cooling it to room temperature in the furnace.
[0014] Preferably, the multi-pass hot rolling forging specifically involves: preheating the homogenized heat-treated ingot to 1050-1100℃, and then performing multi-pass progressive hot rolling forging, with the deformation amount per pass controlled at 15-20% and the total deformation amount ≥85%, to obtain alloy bars.
[0015] Preferably, the gradient wire drawing process specifically involves: after the alloy rod is pickled and polished to remove the surface oxide scale, it is subjected to multiple cold drawing processes with a drawing rate of 2-4 m / min and a single-pass section shrinkage rate controlled at 8-12% to obtain semi-finished steel wire.
[0016] Preferably, the segmented high-temperature annealing modification specifically involves: first heating the semi-finished steel wire to 850-900℃ at a heating rate of 3-5℃ / min and holding it at that temperature for 20-30min; then heating it to 1050-1100℃ at a heating rate of 5-8℃ / min and holding it at that temperature for 15-20min; and finally cooling it to room temperature at a cooling rate of 10-20℃ / min to obtain the steel wire.
[0017] Preferably, the plasma anti-oxidation coating treatment specifically involves: using a plasma spraying process to spray Al2O3-Cr2O3 composite powder onto the surface of the steel wire to form a composite anti-oxidation coating with a thickness of 3-5 μm; the spraying power is 35-40 kW, the spraying distance is 80-100 mm, the main gas argon flow rate is 35-40 L / min, the auxiliary gas hydrogen flow rate is 8-12 L / min, the powder feeding rate is 15-20 g / min, and the spraying scanning speed is 300-400 mm / s; the mass ratio of Al2O3 to Cr2O3 in the Al2O3-Cr2O3 composite powder is 2-3:1-1.2.
[0018] In summary, this application has the following beneficial effects: This application achieves a synergistic strengthening effect by precisely compounding La, Ce, and Y ternary rare earth components and limiting their specific proportions. This allows rare earth atoms to preferentially accumulate at alloy grain boundaries, defect vacancies, and phase interfaces, significantly reducing grain boundary energy and effectively suppressing grain boundary migration and abnormal grain growth during high-temperature service. Simultaneously, the ternary rare earth composite system preferentially reacts with harmful impurities such as O, S, and P in the melt and matrix to generate high-melting-point, highly stable rare earth compounds, effectively eliminating grain boundary embrittlement defects caused by the segregation of harmful impurities at grain boundaries, and significantly purifying and strengthening the grain boundary structure. This ternary rare earth composite system can simultaneously improve the high-temperature grain boundary strength, dislocation movement resistance, and lattice stability of the alloy, significantly improving the high-temperature creep resistance, thermal fatigue resistance, and high-temperature oxidation erosion resistance of stainless steel wire. It solves the technical problems of easy grain boundary weakening, easy microstructure deterioration, and rapid performance degradation of traditional stainless steel wire at high temperatures.
[0019] This application utilizes a limited homogenization heat treatment process to ensure full diffusion of elements within the ingot, eliminate compositional segregation and casting residual defects, uniformly refine grains, and stably control grain size, resulting in a denser and more uniform alloy matrix structure. This ensures the consistency of the mechanical properties and high-temperature resistance of the steel wire from the source, avoiding the defects of uneven structure and large performance fluctuations caused by improper traditional heat treatment parameters.
[0020] This application employs a segmented high-temperature annealing modification process to release residual stress generated during cold wire drawing in a graded and stable manner. This avoids stress concentration caused by rapid temperature changes, while ensuring uniform precipitation of alloy reinforcing phases and optimized grain structure. This effectively eliminates the drawbacks of work hardening and balances the strength and toughness of the steel wire.
[0021] In summary, this application significantly improves the service stability and service life of stainless steel wire under high temperature, high pressure, and alternating load conditions by combining rare earth ratio optimization, precise homogenization heat treatment, and segmented high temperature annealing modification processes, which can meet the stringent operating requirements of turbine outer ring gaskets for aero-engines. Detailed Implementation
[0022] The present application will be further described in detail below with reference to the embodiments.
[0023] The Al2O3 used in the embodiments and comparative examples of this application was purchased from Qinghe County Kangshuo Welding Materials Co., Ltd.; the Cr2O3 was purchased from Taomei New Materials Technology (Shenzhen) Co., Ltd.
[0024] Examples 1-3 provide a high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine and its preparation method.
[0025] Example 1 A high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine, comprising the following chemical composition by mass percentage: C: 0.03%, Cr: 18.0%, Ni: 30.0%, Co: 8.0%, Mo: 2.5%, W: 1.5%, Al: 0.8%, Ti: 1.8%, Nb: 0.5%, Ta: 0.3%, B: 0.005%, Zr: 0.03%, rare earth components: 0.1%, with the balance being Fe and unavoidable impurities. Among the rare earth components, La: 0.04%, Ce: 0.0267%, and Y: 0.0333%.
[0026] A method for preparing high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine includes the following preparation steps: Weigh each raw material component according to the mass percentage and place it in a vacuum induction melting furnace. Vacuum melting is carried out for 40 minutes at a vacuum degree of 0.05 Pa and a temperature of 1580℃. Electromagnetic stirring is used during the melting process at a stirring frequency of 5 Hz. After melting, refining is carried out for 10 minutes at a refining temperature of 1600℃. After refining, the alloy ingot is cast using a water-cooled copper mold at a casting rate of 8 kg / min and a mold cooling water temperature of 25℃ to obtain an alloy ingot with a diameter of 80 mm and a length of 300 mm. The alloy ingot was placed in a heat treatment furnace for homogenization heat treatment. The furnace atmosphere was high-purity argon, the furnace pressure was 0.12 MPa, and the temperature was raised to 1180℃ at a heating rate of 8℃ / min. After holding at this temperature for 8 hours, the furnace was cooled to room temperature to complete the homogenization treatment. The homogenized ingot was preheated to 1050℃ and subjected to multi-pass progressive hot rolling forging. The deformation amount per pass was controlled at 15%, the total deformation amount was 90%, the forging passes were 8, the final forging temperature was 900℃, and the rolling speed was 1.5m / s to obtain an alloy bar with a diameter of 15mm. The alloy rods are pickled in a pickling solution composed of nitric acid, hydrofluoric acid, and deionized water in a mass ratio of 3:1:6. The pickling temperature is 40℃ and the pickling time is 15 minutes to thoroughly remove surface oxide scale, rust, and impurities. After pickling, the rods are rinsed three times with deionized water and dried at 50℃ for 3 hours. After drying, the rods are finely polished with 1200-grit sandpaper to remove surface oxide scale. Then, the rods are cold-drawn in multiple passes using a gradient die at a drawing speed of 2 m / min and a single pass section shrinkage rate controlled at 8%, gradually drawing them into semi-finished steel wires with a diameter of 0.1 mm. The semi-finished steel wire was modified by segmented temperature-controlled annealing. First, the semi-finished steel wire was heated to 850℃ at a heating rate of 3℃ / min and held for 20min. Then, it was heated to 1050℃ at a heating rate of 5℃ / min and held for 15min. Finally, it was cooled to room temperature at a cooling rate of 10℃ / min to obtain the steel wire. Al2O3-Cr2O3 composite powder was sprayed onto the surface of steel wire using a plasma spraying process to form a composite anti-oxidation coating with a thickness of 3μm. The spraying power was 35kW, the spraying distance was 80mm, the main gas argon flow rate was 35L / min, the auxiliary gas hydrogen flow rate was 8L / min, the powder feeding rate was 15g / min, and the spraying scanning speed was 300mm / s. After spraying, the wire was naturally cooled to room temperature to obtain a high-temperature resistant stainless steel wire. The mass ratio of Al2O3 to Cr2O3 in the Al2O3-Cr2O3 composite powder was 2:1.
[0027] Example 2 A high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine, comprising the following chemical composition by mass percentage: C: 0.05%, Cr: 20.0%, Ni: 32.5%, Co: 10%, Mo: 3.2%, W: 2.3%, Al: 1.2%, Ti: 2.3%, Nb: 0.8%, Ta: 0.4%, B: 0.006%, Zr: 0.04%, rare earth components: 0.2%, with the balance being Fe and unavoidable impurities. Among the rare earth components, La: 0.08%, Ce: 0.053%, Y: 0.067%.
[0028] A method for preparing high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine includes the following preparation steps: Weigh each raw material component according to the mass percentage and place it in a vacuum induction melting furnace. Vacuum melting is carried out for 50 minutes at a vacuum degree of 0.04 Pa and a temperature of 1600℃. Electromagnetic stirring is used during the melting process at a stirring frequency of 7 Hz. After melting, refining is carried out for 12 minutes at a refining temperature of 1615℃. After refining, the alloy ingot is cast using a water-cooled copper mold at a casting rate of 10 kg / min and a mold cooling water temperature of 30℃ to obtain an alloy ingot with a diameter of 100 mm and a length of 400 mm. The alloy ingot was placed in a heat treatment furnace for homogenization heat treatment. The furnace atmosphere was high-purity argon, the furnace pressure was 0.14 MPa, and the temperature was raised to 1200℃ at a heating rate of 10℃ / min. After holding at this temperature for 9 hours, the furnace was cooled to room temperature to complete the homogenization treatment. The homogenized ingot was preheated to 1080℃ and subjected to multi-pass progressive hot rolling forging. The deformation amount per pass was controlled at 18%, the total deformation amount was 95%, the forging passes were 10, the final forging temperature was 930℃, and the rolling speed was 2m / s to obtain an alloy bar with a diameter of 20mm. The alloy rods are pickled in a pickling solution composed of nitric acid, hydrofluoric acid, and deionized water in a mass ratio of 3:1:6. The pickling temperature is 45℃ and the pickling time is 20 minutes to thoroughly remove surface oxide scale, rust, and impurities. After pickling, the rods are rinsed four times with deionized water and dried at 70℃ for 4 hours. After drying, the rods are finely polished with 1200-grit sandpaper to remove surface oxide scale. Then, the rods are cold-drawn in multiple passes using a gradient die at a drawing rate of 3 m / min and a single pass section shrinkage rate controlled at 10%, gradually drawing them into semi-finished steel wires with a diameter of 0.2 mm. The semi-finished steel wire was modified by segmented temperature-controlled annealing. First, the semi-finished steel wire was heated to 880℃ at a heating rate of 4℃ / min and held for 25min. Then, it was heated to 1080℃ at a heating rate of 7℃ / min and held for 18min. Finally, it was cooled to room temperature at a cooling rate of 15℃ / min to obtain the steel wire. Plasma spraying was used to coat the surface of steel wire with Al2O3-Cr2O3 composite powder to form a 5μm thick composite anti-oxidation coating. The spraying power was 38kW, the spraying distance was 90mm, the main gas argon flow rate was 38L / min, the auxiliary gas hydrogen flow rate was 10L / min, the powder feeding rate was 18g / min, and the spraying scanning speed was 350mm / s. After spraying, the wire was naturally cooled to room temperature to obtain a high-temperature resistant stainless steel wire. The mass ratio of Al2O3 to Cr2O3 in the Al2O3-Cr2O3 composite powder was 2.5:1.1.
[0029] Example 3 A high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine, comprising the following chemical composition by mass percentage: C: 0.08%, Cr: 22.0%, Ni: 35.0%, Co: 12.0%, Mo: 4.0%, W: 3.0%, Al: 1.5%, Ti: 2.8%, Nb: 1.2%, Ta: 0.5%, B: 0.008%, Zr: 0.05%, rare earth components: 0.3%, with the balance being Fe and unavoidable impurities. Among the rare earth components, La: 0.12%, Ce: 0.08%, and Y: 0.1%.
[0030] A method for preparing high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine includes the following preparation steps: Weigh each raw material component according to the mass percentage and place it in a vacuum induction melting furnace. Vacuum melting is carried out for 60 minutes under vacuum conditions of 0.05 Pa and 1620℃. Electromagnetic stirring is used during the melting process with a stirring frequency of 8 Hz. After melting, refining treatment is carried out for 15 minutes at a refining temperature of 1630℃. After refining, the alloy ingot is cast using a water-cooled copper mold at a casting rate of 12 kg / min and a mold cooling water temperature of 35℃ to obtain an alloy ingot with a diameter of 120 mm and a length of 500 mm. The alloy ingot was placed in a heat treatment furnace for homogenization heat treatment. The furnace atmosphere was high-purity argon, the furnace pressure was 0.15 MPa, and the temperature was raised to 1220℃ at a heating rate of 12℃ / min. After holding at this temperature for 10 hours, the ingot was cooled to room temperature with the furnace to complete the homogenization treatment. The homogenized ingot was preheated to 1100℃ and subjected to multi-pass progressive hot rolling forging. The deformation amount per pass was controlled at 20%, the total deformation amount was 95%, the forging passes were 12, the final forging temperature was 950℃, and the rolling speed was 2.5m / s, to obtain an alloy bar with a diameter of 25mm. The alloy rods are pickled in a pickling solution composed of nitric acid, hydrofluoric acid, and deionized water in a mass ratio of 3:1:6. The pickling temperature is 50℃ and the pickling time is 25 minutes to thoroughly remove surface oxide scale, rust, and impurities. After pickling, the rods are rinsed five times with deionized water and dried at 70℃ for 5 hours. After drying, the rods are finely polished with 1200-grit sandpaper to remove surface oxide scale. Then, the rods are cold-drawn in multiple passes using a gradient die at a drawing rate of 4 m / min and a single pass section shrinkage rate controlled at 12%, gradually drawing them into semi-finished steel wires with a diameter of 0.3 mm. The semi-finished steel wire was modified by segmented temperature-controlled annealing. First, the semi-finished steel wire was heated to 900℃ at a heating rate of 5℃ / min and held for 30min. Then, it was heated to 1100℃ at a heating rate of 8℃ / min and held for 20min. Finally, it was cooled to room temperature at a cooling rate of 20℃ / min to obtain the steel wire. Plasma spraying was used to coat the surface of steel wire with Al2O3-Cr2O3 composite powder to form a 5μm thick composite anti-oxidation coating. The spraying power was 40kW, the spraying distance was 100mm, the main gas argon flow rate was 40L / min, the auxiliary gas hydrogen flow rate was 12L / min, the powder feeding rate was 20g / min, and the spraying scanning speed was 400mm / s. After spraying, the wire was naturally cooled to room temperature to obtain a high-temperature resistant stainless steel wire. The mass ratio of Al2O3 to Cr2O3 in the Al2O3-Cr2O3 composite powder was 3:1.2.
[0031] Comparative Example 1 A high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine, comprising the following chemical composition by mass percentage: C: 0.03%, Cr: 18.0%, Ni: 30.0%, Co: 8.0%, Mo: 2.5%, W: 1.5%, Al: 0.8%, Ti: 1.8%, Nb: 0.5%, Ta: 0.3%, B: 0.005%, Zr: 0.03%, rare earth components: 0.1%, with the balance being Fe and unavoidable impurities. Among the rare earth components, La: 0.03%, Ce: 0.02%, and Y: 0.05%.
[0032] A method for preparing high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine includes the following preparation steps: Weigh each raw material component according to the mass percentage and place it in a vacuum induction melting furnace. Vacuum melting is carried out for 40 minutes at a vacuum degree of 0.05 Pa and a temperature of 1580℃. Electromagnetic stirring is used during the melting process at a stirring frequency of 5 Hz. After melting, refining is carried out for 10 minutes at a refining temperature of 1600℃. After refining, the alloy ingot is cast using a water-cooled copper mold at a casting rate of 8 kg / min and a mold cooling water temperature of 25℃ to obtain an alloy ingot with a diameter of 80 mm and a length of 300 mm. The alloy ingot was placed in a heat treatment furnace for homogenization heat treatment. The furnace atmosphere was high-purity argon, the furnace pressure was 0.12 MPa, and the temperature was raised to 1180℃ at a heating rate of 8℃ / min. After holding at this temperature for 8 hours, the furnace was cooled to room temperature to complete the homogenization treatment. The homogenized ingot was preheated to 1050℃ and subjected to multi-pass progressive hot rolling forging. The deformation amount per pass was controlled at 15%, the total deformation amount was 90%, the forging passes were 8, the final forging temperature was 900℃, and the rolling speed was 1.5m / s to obtain an alloy bar with a diameter of 15mm. The alloy rods are pickled in a pickling solution composed of nitric acid, hydrofluoric acid, and deionized water in a mass ratio of 3:1:6. The pickling temperature is 40℃ and the pickling time is 15 minutes to thoroughly remove surface oxide scale, rust, and impurities. After pickling, the rods are rinsed three times with deionized water and dried at 50℃ for 3 hours. After drying, the rods are finely polished with 1200-grit sandpaper to remove surface oxide scale. Then, the rods are cold-drawn in multiple passes using a gradient die at a drawing speed of 2 m / min and a single pass section shrinkage rate controlled at 8%, gradually drawing them into semi-finished steel wires with a diameter of 0.1 mm. The semi-finished steel wire was modified by segmented temperature-controlled annealing. First, the semi-finished steel wire was heated to 850℃ at a heating rate of 3℃ / min and held for 20min. Then, it was heated to 1050℃ at a heating rate of 5℃ / min and held for 15min. Finally, it was cooled to room temperature at a cooling rate of 10℃ / min to obtain the steel wire. Al2O3-Cr2O3 composite powder was sprayed onto the surface of steel wire using a plasma spraying process to form a composite anti-oxidation coating with a thickness of 3μm. The spraying power was 35kW, the spraying distance was 80mm, the main gas argon flow rate was 35L / min, the auxiliary gas hydrogen flow rate was 8L / min, the powder feeding rate was 15g / min, and the spraying scanning speed was 300mm / s. After spraying, the wire was naturally cooled to room temperature to obtain a high-temperature resistant stainless steel wire. The mass ratio of Al2O3 to Cr2O3 in the Al2O3-Cr2O3 composite powder was 2:1.
[0033] Comparative Example 2 A high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine, comprising the following chemical composition by mass percentage: C: 0.03%, Cr: 18.0%, Ni: 30.0%, Co: 8.0%, Mo: 2.5%, W: 1.5%, Al: 0.8%, Ti: 1.8%, Nb: 0.5%, Ta: 0.3%, B: 0.005%, Zr: 0.03%, rare earth components: 0.1%, with the balance being Fe and unavoidable impurities. Among the rare earth components, La: 0.0167%, Ce: 0.05%, and Y: 0.0333%.
[0034] A method for preparing high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine includes the following preparation steps: Weigh each raw material component according to the mass percentage and place it in a vacuum induction melting furnace. Vacuum melting is carried out for 40 minutes at a vacuum degree of 0.05 Pa and a temperature of 1580℃. Electromagnetic stirring is used during the melting process at a stirring frequency of 5 Hz. After melting, refining is carried out for 10 minutes at a refining temperature of 1600℃. After refining, the alloy ingot is cast using a water-cooled copper mold at a casting rate of 8 kg / min and a mold cooling water temperature of 25℃ to obtain an alloy ingot with a diameter of 80 mm and a length of 300 mm. The alloy ingot was placed in a heat treatment furnace for homogenization heat treatment. The furnace atmosphere was high-purity argon, the furnace pressure was 0.12 MPa, and the temperature was raised to 1180℃ at a heating rate of 8℃ / min. After holding at this temperature for 8 hours, the furnace was cooled to room temperature to complete the homogenization treatment. The homogenized ingot was preheated to 1050℃ and subjected to multi-pass progressive hot rolling forging. The deformation amount per pass was controlled at 15%, the total deformation amount was 90%, the forging passes were 8, the final forging temperature was 900℃, and the rolling speed was 1.5m / s to obtain an alloy bar with a diameter of 15mm. The alloy rods are pickled in a pickling solution composed of nitric acid, hydrofluoric acid, and deionized water in a mass ratio of 3:1:6. The pickling temperature is 40℃ and the pickling time is 15 minutes to thoroughly remove surface oxide scale, rust, and impurities. After pickling, the rods are rinsed three times with deionized water and dried at 50℃ for 3 hours. After drying, the rods are finely polished with 1200-grit sandpaper to remove surface oxide scale. Then, the rods are cold-drawn in multiple passes using a gradient die at a drawing speed of 2 m / min and a single pass section shrinkage rate controlled at 8%, gradually drawing them into semi-finished steel wires with a diameter of 0.1 mm. The semi-finished steel wire was modified by segmented temperature-controlled annealing. First, the semi-finished steel wire was heated to 850℃ at a heating rate of 3℃ / min and held for 20min. Then, it was heated to 1050℃ at a heating rate of 5℃ / min and held for 15min. Finally, it was cooled to room temperature at a cooling rate of 10℃ / min to obtain the steel wire. Al2O3-Cr2O3 composite powder was sprayed onto the surface of steel wire using a plasma spraying process to form a composite anti-oxidation coating with a thickness of 3μm. The spraying power was 35kW, the spraying distance was 80mm, the main gas argon flow rate was 35L / min, the auxiliary gas hydrogen flow rate was 8L / min, the powder feeding rate was 15g / min, and the spraying scanning speed was 300mm / s. After spraying, the wire was naturally cooled to room temperature to obtain a high-temperature resistant stainless steel wire. The mass ratio of Al2O3 to Cr2O3 in the Al2O3-Cr2O3 composite powder was 2:1.
[0035] Comparative Example 3 A high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine, comprising the following chemical composition by mass percentage: C: 0.03%, Cr: 18.0%, Ni: 30.0%, Co: 8.0%, Mo: 2.5%, W: 1.5%, Al: 0.8%, Ti: 1.8%, Nb: 0.5%, Ta: 0.3%, B: 0.005%, Zr: 0.03%, rare earth components: 0.1%, with the balance being Fe and unavoidable impurities. Among the rare earth components, La: 0.01%, Ce: 0.01%, and Y: 0.08%.
[0036] A method for preparing high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine includes the following preparation steps: Weigh each raw material component according to the mass percentage and place it in a vacuum induction melting furnace. Vacuum melting is carried out for 40 minutes at a vacuum degree of 0.05 Pa and a temperature of 1580℃. Electromagnetic stirring is used during the melting process at a stirring frequency of 5 Hz. After melting, refining is carried out for 10 minutes at a refining temperature of 1600℃. After refining, the alloy ingot is cast using a water-cooled copper mold at a casting rate of 8 kg / min and a mold cooling water temperature of 25℃ to obtain an alloy ingot with a diameter of 80 mm and a length of 300 mm. The alloy ingot was placed in a heat treatment furnace for homogenization heat treatment. The furnace atmosphere was high-purity argon, the furnace pressure was 0.12 MPa, and the temperature was raised to 1180℃ at a heating rate of 8℃ / min. After holding at this temperature for 8 hours, the furnace was cooled to room temperature to complete the homogenization treatment. The homogenized ingot was preheated to 1050℃ and subjected to multi-pass progressive hot rolling forging. The deformation amount per pass was controlled at 15%, the total deformation amount was 90%, the forging passes were 8, the final forging temperature was 900℃, and the rolling speed was 1.5m / s to obtain an alloy bar with a diameter of 15mm. The alloy rods are pickled in a pickling solution composed of nitric acid, hydrofluoric acid, and deionized water in a mass ratio of 3:1:6. The pickling temperature is 40℃ and the pickling time is 15 minutes to thoroughly remove surface oxide scale, rust, and impurities. After pickling, the rods are rinsed three times with deionized water and dried at 50℃ for 3 hours. After drying, the rods are finely polished with 1200-grit sandpaper to remove surface oxide scale. Then, the rods are cold-drawn in multiple passes using a gradient die at a drawing speed of 2 m / min and a single pass section shrinkage rate controlled at 8%, gradually drawing them into semi-finished steel wires with a diameter of 0.1 mm. The semi-finished steel wire was modified by segmented temperature-controlled annealing. First, the semi-finished steel wire was heated to 850℃ at a heating rate of 3℃ / min and held for 20min. Then, it was heated to 1050℃ at a heating rate of 5℃ / min and held for 15min. Finally, it was cooled to room temperature at a cooling rate of 10℃ / min to obtain the steel wire. Al2O3-Cr2O3 composite powder was sprayed onto the surface of steel wire using a plasma spraying process to form a composite anti-oxidation coating with a thickness of 3μm. The spraying power was 35kW, the spraying distance was 80mm, the main gas argon flow rate was 35L / min, the auxiliary gas hydrogen flow rate was 8L / min, the powder feeding rate was 15g / min, and the spraying scanning speed was 300mm / s. After spraying, the wire was naturally cooled to room temperature to obtain a high-temperature resistant stainless steel wire. The mass ratio of Al2O3 to Cr2O3 in the Al2O3-Cr2O3 composite powder was 2:1.
[0037] Comparative Example 4 A high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine, comprising the following chemical composition by mass percentage: C: 0.03%, Cr: 18.0%, Ni: 30.0%, Co: 8.0%, Mo: 2.5%, W: 1.5%, Al: 0.8%, Ti: 1.8%, Nb: 0.5%, Ta: 0.3%, B: 0.005%, Zr: 0.03%, rare earth components: 0.1%, with the balance being Fe and unavoidable impurities. Among the rare earth components, La: 0.04%, Ce: 0.0267%, and Y: 0.0333%.
[0038] A method for preparing high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine includes the following preparation steps: Weigh each raw material component according to the mass percentage and place it in a vacuum induction melting furnace. Vacuum melting is carried out for 40 minutes at a vacuum degree of 0.05 Pa and a temperature of 1580℃. Electromagnetic stirring is used during the melting process at a stirring frequency of 5 Hz. After melting, refining is carried out for 10 minutes at a refining temperature of 1600℃. After refining, the alloy ingot is cast using a water-cooled copper mold at a casting rate of 8 kg / min and a mold cooling water temperature of 25℃ to obtain an alloy ingot with a diameter of 80 mm and a length of 300 mm. The alloy ingot was placed in a heat treatment furnace for homogenization heat treatment. The furnace atmosphere was high-purity argon, the furnace pressure was 0.12 MPa, and the temperature was raised to 1180℃ at a heating rate of 8℃ / min. After holding at this temperature for 8 hours, the furnace was cooled to room temperature to complete the homogenization treatment. The homogenized ingot was preheated to 1050℃ and subjected to multi-pass progressive hot rolling forging. The deformation amount per pass was controlled at 15%, the total deformation amount was 90%, the forging passes were 8, the final forging temperature was 900℃, and the rolling speed was 1.5m / s to obtain an alloy bar with a diameter of 15mm. The alloy rods are pickled in a pickling solution composed of nitric acid, hydrofluoric acid, and deionized water in a mass ratio of 3:1:6. The pickling temperature is 40℃ and the pickling time is 15 minutes to thoroughly remove surface oxide scale, rust, and impurities. After pickling, the rods are rinsed three times with deionized water and dried at 50℃ for 3 hours. After drying, the rods are finely polished with 1200-grit sandpaper to remove surface oxide scale. Then, the rods are cold-drawn in multiple passes using a gradient die at a drawing speed of 2 m / min and a single pass section shrinkage rate controlled at 8%, gradually drawing them into semi-finished steel wires with a diameter of 0.1 mm. The semi-finished steel wire was modified by segmented temperature-controlled annealing. First, the semi-finished steel wire was heated to 850℃ at a heating rate of 1℃ / min and held for 20min. Then, it was heated to 1050℃ at a heating rate of 12℃ / min and held for 15min. Finally, it was cooled to room temperature at a cooling rate of 10℃ / min to obtain the steel wire. Al2O3-Cr2O3 composite powder was sprayed onto the surface of steel wire using a plasma spraying process to form a composite anti-oxidation coating with a thickness of 3μm. The spraying power was 35kW, the spraying distance was 80mm, the main gas argon flow rate was 35L / min, the auxiliary gas hydrogen flow rate was 8L / min, the powder feeding rate was 15g / min, and the spraying scanning speed was 300mm / s. After spraying, the wire was naturally cooled to room temperature to obtain a high-temperature resistant stainless steel wire. The mass ratio of Al2O3 to Cr2O3 in the Al2O3-Cr2O3 composite powder was 2:1.
[0039] Comparative Example 5 A high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine, comprising the following chemical composition by mass percentage: C: 0.03%, Cr: 18.0%, Ni: 30.0%, Co: 8.0%, Mo: 2.5%, W: 1.5%, Al: 0.8%, Ti: 1.8%, Nb: 0.5%, Ta: 0.3%, B: 0.005%, Zr: 0.03%, rare earth components: 0.1%, with the balance being Fe and unavoidable impurities. Among the rare earth components, La: 0.04%, Ce: 0.0267%, and Y: 0.0333%.
[0040] A method for preparing high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine includes the following preparation steps: Weigh each raw material component according to the mass percentage and place it in a vacuum induction melting furnace. Vacuum melting is carried out for 40 minutes at a vacuum degree of 0.05 Pa and a temperature of 1580℃. Electromagnetic stirring is used during the melting process at a stirring frequency of 5 Hz. After melting, refining is carried out for 10 minutes at a refining temperature of 1600℃. After refining, the alloy ingot is cast using a water-cooled copper mold at a casting rate of 8 kg / min and a mold cooling water temperature of 25℃ to obtain an alloy ingot with a diameter of 80 mm and a length of 300 mm. The alloy ingot was placed in a heat treatment furnace for homogenization heat treatment. The furnace atmosphere was high-purity argon, the furnace pressure was 0.12 MPa, and the temperature was raised to 1180℃ at a heating rate of 8℃ / min. After holding at this temperature for 8 hours, the furnace was cooled to room temperature to complete the homogenization treatment. The homogenized ingot was preheated to 1050℃ and subjected to multi-pass progressive hot rolling forging. The deformation amount per pass was controlled at 15%, the total deformation amount was 90%, the forging passes were 8, the final forging temperature was 900℃, and the rolling speed was 1.5m / s to obtain an alloy bar with a diameter of 15mm. The alloy rods are pickled in a pickling solution composed of nitric acid, hydrofluoric acid, and deionized water in a mass ratio of 3:1:6. The pickling temperature is 40℃ and the pickling time is 15 minutes to thoroughly remove surface oxide scale, rust, and impurities. After pickling, the rods are rinsed three times with deionized water and dried at 50℃ for 3 hours. After drying, the rods are finely polished with 1200-grit sandpaper to remove surface oxide scale. Then, the rods are cold-drawn in multiple passes using a gradient die at a drawing speed of 2 m / min and a single pass section shrinkage rate controlled at 8%, gradually drawing them into semi-finished steel wires with a diameter of 0.1 mm. The semi-finished steel wire was modified by segmented temperature-controlled annealing. First, the semi-finished steel wire was heated to 850℃ at a heating rate of 3℃ / min and held for 20min. Then, it was heated to 1050℃ at a heating rate of 5℃ / min and held for 15min. Finally, it was cooled to room temperature at a cooling rate of 40℃ / min to obtain the steel wire. Al2O3-Cr2O3 composite powder was sprayed onto the surface of steel wire using a plasma spraying process to form a composite anti-oxidation coating with a thickness of 3μm. The spraying power was 35kW, the spraying distance was 80mm, the main gas argon flow rate was 35L / min, the auxiliary gas hydrogen flow rate was 8L / min, the powder feeding rate was 15g / min, and the spraying scanning speed was 300mm / s. After spraying, the wire was naturally cooled to room temperature to obtain a high-temperature resistant stainless steel wire. The mass ratio of Al2O3 to Cr2O3 in the Al2O3-Cr2O3 composite powder was 2:1.
[0041] Comparative Example 6 A high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine, comprising the following chemical composition by mass percentage: C: 0.03%, Cr: 18.0%, Ni: 30.0%, Co: 8.0%, Mo: 2.5%, W: 1.5%, Al: 0.8%, Ti: 1.8%, Nb: 0.5%, Ta: 0.3%, B: 0.005%, Zr: 0.03%, rare earth components: 0.1%, with the balance being Fe and unavoidable impurities. Among the rare earth components, La: 0.04%, Ce: 0.0267%, and Y: 0.0333%.
[0042] A method for preparing high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine includes the following preparation steps: Weigh each raw material component according to the mass percentage and place it in a vacuum induction melting furnace. Vacuum melting is carried out for 40 minutes at a vacuum degree of 0.05 Pa and a temperature of 1580℃. Electromagnetic stirring is used during the melting process at a stirring frequency of 5 Hz. After melting, refining is carried out for 10 minutes at a refining temperature of 1600℃. After refining, the alloy ingot is cast using a water-cooled copper mold at a casting rate of 8 kg / min and a mold cooling water temperature of 25℃ to obtain an alloy ingot with a diameter of 80 mm and a length of 300 mm. The alloy ingot was placed in a heat treatment furnace for homogenization heat treatment. The furnace atmosphere was high-purity argon, the furnace pressure was 0.12 MPa, and the temperature was raised to 1180℃ at a heating rate of 5℃ / min. After holding at this temperature for 8 hours, the furnace was cooled to room temperature to complete the homogenization treatment. The homogenized ingot was preheated to 1050℃ and subjected to multi-pass progressive hot rolling forging. The deformation amount per pass was controlled at 15%, the total deformation amount was 90%, the forging passes were 8, the final forging temperature was 900℃, and the rolling speed was 1.5m / s to obtain an alloy bar with a diameter of 15mm. The alloy rods are pickled in a pickling solution composed of nitric acid, hydrofluoric acid, and deionized water in a mass ratio of 3:1:6. The pickling temperature is 40℃ and the pickling time is 15 minutes to thoroughly remove surface oxide scale, rust, and impurities. After pickling, the rods are rinsed three times with deionized water and dried at 50℃ for 3 hours. After drying, the rods are finely polished with 1200-grit sandpaper to remove surface oxide scale. Then, the rods are cold-drawn in multiple passes using a gradient die at a drawing speed of 2 m / min and a single pass section shrinkage rate controlled at 8%, gradually drawing them into semi-finished steel wires with a diameter of 0.1 mm. The semi-finished steel wire was modified by segmented temperature-controlled annealing. First, the semi-finished steel wire was heated to 850℃ at a heating rate of 3℃ / min and held for 20min. Then, it was heated to 1050℃ at a heating rate of 5℃ / min and held for 15min. Finally, it was cooled to room temperature at a cooling rate of 10℃ / min to obtain the steel wire. Al2O3-Cr2O3 composite powder was sprayed onto the surface of steel wire using a plasma spraying process to form a composite anti-oxidation coating with a thickness of 3μm. The spraying power was 35kW, the spraying distance was 80mm, the main gas argon flow rate was 35L / min, the auxiliary gas hydrogen flow rate was 8L / min, the powder feeding rate was 15g / min, and the spraying scanning speed was 300mm / s. After spraying, the wire was naturally cooled to room temperature to obtain a high-temperature resistant stainless steel wire. The mass ratio of Al2O3 to Cr2O3 in the Al2O3-Cr2O3 composite powder was 2:1.
[0043] Comparative Example 7 A high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine, comprising the following chemical composition by mass percentage: C: 0.03%, Cr: 18.0%, Ni: 30.0%, Co: 8.0%, Mo: 2.5%, W: 1.5%, Al: 0.8%, Ti: 1.8%, Nb: 0.5%, Ta: 0.3%, B: 0.005%, Zr: 0.03%, rare earth components: 0.1%, with the balance being Fe and unavoidable impurities. Among the rare earth components, La: 0.04%, Ce: 0.0267%, and Y: 0.0333%.
[0044] A method for preparing high-temperature resistant stainless steel wire for an outer ring seal gasket of an aero-engine turbine includes the following preparation steps: Weigh each raw material component according to the mass percentage and place it in a vacuum induction melting furnace. Vacuum melting is carried out for 40 minutes at a vacuum degree of 0.05 Pa and a temperature of 1580℃. Electromagnetic stirring is used during the melting process at a stirring frequency of 5 Hz. After melting, refining is carried out for 10 minutes at a refining temperature of 1600℃. After refining, the alloy ingot is cast using a water-cooled copper mold at a casting rate of 8 kg / min and a mold cooling water temperature of 25℃ to obtain an alloy ingot with a diameter of 80 mm and a length of 300 mm. The alloy ingot was placed in a heat treatment furnace for homogenization heat treatment. The furnace atmosphere was high-purity argon, the furnace pressure was 0.12 MPa, and the temperature was raised to 1180℃ at a heating rate of 8℃ / min. After holding at this temperature for 8 hours, the furnace was cooled to room temperature to complete the homogenization treatment. The homogenized ingot was preheated to 1050℃ and subjected to multi-pass progressive hot rolling forging. The deformation amount per pass was controlled at 15%, the total deformation amount was 90%, the forging passes were 8, the final forging temperature was 900℃, and the rolling speed was 1.5m / s to obtain an alloy bar with a diameter of 15mm. The alloy rods are pickled in a pickling solution composed of nitric acid, hydrofluoric acid, and deionized water in a mass ratio of 3:1:6. The pickling temperature is 40℃ and the pickling time is 15 minutes to thoroughly remove surface oxide scale, rust, and impurities. After pickling, the rods are rinsed three times with deionized water and dried at 50℃ for 3 hours. After drying, the rods are finely polished with 1200-grit sandpaper to remove surface oxide scale. Then, the rods are cold-drawn in multiple passes using a gradient die at a drawing speed of 2 m / min and a single pass section shrinkage rate controlled at 8%, gradually drawing them into semi-finished steel wires with a diameter of 0.1 mm. The semi-finished steel wire is modified by segmented temperature-controlled annealing. First, the semi-finished steel wire is heated to 1050℃ at a heating rate of 3℃ / min, held at that temperature for 35min, and then naturally cooled to room temperature to obtain the steel wire. Al2O3-Cr2O3 composite powder was sprayed onto the surface of steel wire using a plasma spraying process to form a composite anti-oxidation coating with a thickness of 3μm. The spraying power was 35kW, the spraying distance was 80mm, the main gas argon flow rate was 35L / min, the auxiliary gas hydrogen flow rate was 8L / min, the powder feeding rate was 15g / min, and the spraying scanning speed was 300mm / s. After spraying, the wire was naturally cooled to room temperature to obtain a high-temperature resistant stainless steel wire. The mass ratio of Al2O3 to Cr2O3 in the Al2O3-Cr2O3 composite powder was 2:1.
[0045] Performance testing The performance of the high-temperature resistant stainless steel wires used for the turbine outer ring sealing gaskets of aero-engines prepared in Examples 1-3 and Comparative Examples 1-7 of this application was tested. The specific test contents are as follows: High-temperature tensile strength: Referring to the national standard GB / T 228.2-2015 "Metallic materials, tensile testing - Part 2: High-temperature test method", the stainless steel wire specimens prepared in Examples 1-3 and Comparative Examples 1-7 were placed in a high-temperature tensile testing machine and heated to 1100℃ at a rate of 5℃ / min. The specimens were held at 1100℃ for 15 min to ensure that the overall temperature of the specimens was uniform and stable. Uniaxial tensile tests were conducted at a constant test rate of 2 mm / min to determine the high-temperature tensile strength of the specimens. Each group of specimens was tested 5 times, and the arithmetic mean was taken as the final test result. Creep deformation: Referring to the national standard GB / T 2039-2024 "Metallic Materials Uniaxial Tensile Creep Test Method", the stainless steel wire specimens prepared in Examples 1-3 and Comparative Examples 1-7 were installed in a high-temperature creep testing machine. The test temperature was set to 1100℃ and the constant tensile stress was 80MPa. The constant temperature and constant load test was conducted for 100h. The specimen deformation data was recorded. After the test, the total creep deformation of the specimen was measured. Oxidation weight gain: Referring to the national standard GB / T 38430-2019 "Corrosion of metals and alloys - Isothermal exposure oxidation test method for metallic materials under high temperature corrosion conditions", the stainless steel wire samples prepared in Examples 1-3 and Comparative Examples 1-7 were placed in a high-temperature muffle furnace and isothermally exposed at 1100℃ in air atmosphere for 100h. After the test, the samples were taken out, cooled to room temperature, cleaned of surface dust, weighed, and the oxidation weight gain per unit area was calculated. Coating peeling rate after thermal shock: Referring to the national standard GB / T 38231-2019 "Corrosion of metals and alloys - Thermal cycling exposure oxidation test under high temperature corrosion conditions", a high temperature-room temperature thermal shock test was adopted. The parameters for a single cycle were: placing the sample in a 950℃ high temperature furnace for 10 min, immersing the sample in room temperature water, and rapidly water cooling to room temperature. The duration of a single cycle was 20 min, and 100 cycles were performed continuously. After the test, the proportion of the peeled area to the total surface area was counted, and the coating peeling rate was calculated. Repeated bending fracture count: Referring to the national standard GB / T 238-2013 "Metallic materials wire repeated bending test method", the wire repeated bending test machine was used to perform 90° forward and reverse repeated bending test on the sample, and the number of repeated bending fracture counts when the sample completely broke was recorded. Stress relaxation retention rate: Referring to the national standard GB / T 10120-2013 "Metallic materials, tensile stress relaxation test method", at room temperature, a constant elastic initial tensile strain of 0.5% was applied to the stainless steel wire specimen and the tensile displacement of the specimen was locked to ensure that the overall strain of the specimen was constant, and the initial stress value was recorded; then the temperature was raised to 900℃ and held at a constant temperature for 100h, and the change of residual stress of the specimen was monitored in real time throughout the process, and the stress relaxation retention rate was calculated. The test results are shown in Table 1.
[0046] Table 1. Performance parameters of the high-temperature resistant stainless steel wires prepared in Examples 1-3 and Comparative Examples 1-7. As shown in Table 1, the high-temperature resistant stainless steel wires for aero-engine turbine outer ring sealing gaskets prepared in Examples 1-3 of this application exhibit excellent comprehensive performance. By optimizing the alloy element ratio and rare earth component doping ratio, and combining this with precise and controllable vacuum melting, homogenization heat treatment, wire drawing, and coating spraying processes, the comprehensive performance of the stainless steel wires is significantly improved. It exhibits higher tensile strength at 1100℃, lower high-temperature creep deformation, and excellent high-temperature structural stability. Furthermore, the high-temperature oxidation weight gain and coating peeling rate after thermal shock are far lower than in the comparative examples, demonstrating outstanding oxidation resistance and thermal shock resistance. Simultaneously, the product demonstrates a high number of repeated bending fracture cycles and a high stress relaxation retention rate, significantly improving mechanical toughness and high-temperature stress retention performance. This effectively solves the defects of traditional stainless steel wires, such as easy deformation at high temperatures, oxidation peeling, fatigue fracture, and rapid stress decay. It can meet the harsh high-temperature service conditions of aero-engine turbine outer ring sealing gaskets, and its service life and operational stability are significantly improved.
[0047] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A high-temperature resistant stainless steel wire for a turbine outer ring sealing gasket in an aero-engine, characterized in that, By mass percentage, the chemical composition includes the following: C: 0.03-0.08%, Cr: 18.0-22.0%, Ni: 30.0-35.0%, Co: 8.0-12.0%, Mo: 2.5-4.0%, W: 1.5-3.0%, Al: 0.8-1.5%, Ti: 1.8-2.8%, Nb: 0.5-1.2%, Ta: 0.3-0.5%, B: 0.005-0.008%, Zr: 0.03-0.05%, rare earth components: 0.1-0.3%, balance being Fe and unavoidable impurities.
2. The high-temperature resistant stainless steel wire for the outer ring sealing gasket of an aero-engine turbine according to claim 1, characterized in that, In the rare earth component, the mass ratio of La, Ce, and Y satisfies: 2m Ce =3m La , and 2m Y =m La +m Ce ; Where, m La m Ce m Y These represent the masses of La, Ce, and Y in the rare earth components, respectively.
3. The high-temperature resistant stainless steel wire for the outer ring sealing gasket of an aero-engine turbine according to claim 1, characterized in that, The stainless steel wire comprises, by mass percentage, the following chemical composition: C: 0.03-0.06%, Cr: 19.0-21.0%, Ni: 32.0-33.0%, Co: 9.0-11.0%, Mo: 2.8-3.5%, W: 2.2-2.8%, Al: 1.0-1.3%, Ti: 2.0-2.5%, Nb: 0.7-0.9%, Ta: 0.35-0.45%, B: 0.006-0.007%, Zr: 0.035-0.045%, rare earth components: 0.15-0.25%, with the balance being Fe and unavoidable impurities.
4. A method for preparing high-temperature resistant stainless steel wire for an aero-engine turbine outer ring sealing gasket as described in any one of claims 1-3, characterized in that, The preparation steps include the following: Each raw material component is weighed according to mass percentage, and then successively subjected to vacuum melting and casting, homogenization heat treatment, multi-pass hot rolling forging, gradient wire drawing, segmented high-temperature annealing modification, and plasma anti-oxidation coating treatment to obtain high-temperature resistant stainless steel wire for turbine outer ring sealing gaskets of aero-engines.
5. The method for preparing high-temperature resistant stainless steel wire for the outer ring sealing gasket of an aero-engine turbine according to claim 4, characterized in that, The vacuum melting and casting of the ingot specifically involves: vacuum melting for 40-60 minutes under vacuum conditions of ≤0.05Pa and 1580-1620℃, followed by refining and casting to obtain an alloy ingot.
6. The method for preparing high-temperature resistant stainless steel wire for the outer ring sealing gasket of an aero-engine turbine according to claim 4, characterized in that, The homogenization heat treatment specifically involves heating the alloy ingot to 1180-1220℃ at a heating rate of 8-12℃ / min, holding it at that temperature for 8-10 hours, and then cooling it to room temperature in the furnace.
7. The method for preparing high-temperature resistant stainless steel wire for the outer ring sealing gasket of an aero-engine turbine according to claim 4, characterized in that, The multi-pass hot rolling forging specifically involves: preheating the homogenized heat-treated ingot to 1050-1100℃, and then performing multi-pass progressive hot rolling forging, with the deformation amount of a single pass controlled at 15-20% and the total deformation amount ≥85%, to obtain alloy bars.
8. The method for preparing high-temperature resistant stainless steel wire for the outer ring sealing gasket of an aero-engine turbine according to claim 4, characterized in that, The gradient wire drawing process specifically involves: after the alloy rod is pickled and polished to remove the surface oxide scale, it undergoes multiple cold drawing processes with a drawing rate of 2-4 m / min and a single-pass section shrinkage rate controlled at 8-12%, to obtain semi-finished steel wire.
9. The method for preparing high-temperature resistant stainless steel wire for the outer ring sealing gasket of an aero-engine turbine according to claim 4, characterized in that, The segmented high-temperature annealing modification is specifically as follows: first, the semi-finished steel wire is heated to 850-900℃ at a heating rate of 3-5℃ / min and held for 20-30min; then, it is heated to 1050-1100℃ at a heating rate of 5-8℃ / min and held for 15-20min; finally, it is cooled to room temperature at a cooling rate of 10-20℃ / min to obtain the steel wire.
10. The method for preparing high-temperature resistant stainless steel wire for the outer ring sealing gasket of an aero-engine turbine according to claim 4, characterized in that, The plasma anti-oxidation coating treatment specifically involves: using a plasma spraying process to spray Al2O3-Cr2O3 composite powder onto the surface of the steel wire to form a composite anti-oxidation coating with a thickness of 3-5 μm. The spraying power is 35-40 kW, the spraying distance is 80-100 mm, the main gas argon flow rate is 35-40 L / min, the auxiliary gas hydrogen flow rate is 8-12 L / min, the powder feeding rate is 15-20 g / min, and the spraying scanning speed is 300-400 mm / s. The mass ratio of Al2O3 to Cr2O3 in the Al2O3-Cr2O3 composite powder is 2-3:1-1.2.